2005
DOI: 10.1074/jbc.m409507200
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Aβ40 Studied by NMR at Low pH Reveals That Sodium 4,4-Dimethyl-4-silapentane-1-sulfonate (DSS) Binds and Promotes β-Ball Oligomerization

Abstract: The Alzheimer's A␤40 peptide forms soluble oligomers that are extremely potent neurotoxins and strongly impede synapses function. In this study the formation and structure of the large, soluble, neurotoxic A␤40 oligomer called "␤-ball" were characterized by two-dimensional NMR, circular dichroism, fluorescence spectroscopy, hydrogen exchange, and equilibrium sedimentation. In acidic aqueous solution, half the A␤40 molecules are in the ␤-ball state; the remainder are monomeric. The equilibrium between the two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…[8,9,36] Models representing several possible structures of aggregated forms have been proposed very recently. These range in size from dimers to 200-mer spherical b-balls; [13] but aggregation of helical peptides is a widespread mechanism-from antibiotic peptides to virus fusion peptides-that leads to membrane poration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8,9,36] Models representing several possible structures of aggregated forms have been proposed very recently. These range in size from dimers to 200-mer spherical b-balls; [13] but aggregation of helical peptides is a widespread mechanism-from antibiotic peptides to virus fusion peptides-that leads to membrane poration.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the natural abundance of 13 C, 13 C-HSQC experiments were also acquired with the samples in the HFIP/H 2 O mixtures with a ratio 30:70 and 80:20. Experiments were collected in phase-sensitive mode [45,46] by using water gradient suppression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further understand the link between folding and aggregation in A␤, we probed the structural features of residues around 24-28. Solution NMR data of A␤ and A␤(1-42) suggested turn-like structures in residues 20-26 (4) or a turn in residues 22-25 (27). Solution NMR data of A␤(10-35) (24) and A␤(21-30) (28) indicated a double turn in residues 22-27 and 24-28, respectively.…”
mentioning
confidence: 99%
“…Whereas an intramolecular salt bridge between Asp-23 and Lys-28 was proposed for the fibrils of A␤(1-40) (20), the same salt bridge was suggested to be intermolecular in the fibrils of A␤(1-42) (21). The stability of the turn (24)(25)(26)(27) in A␤(10-35) and the turn (24)(25)(26)(27)(28) in A␤(21-30) has previously been tested in simulation studies (29,30) using the respective NMR structure models (24,28). The simulation study of A␤(21-30) also revealed a salt bridge between Glu-22 and Lys-28 (30).…”
mentioning
confidence: 99%